Forest structure and tree species composition at Kuala Langat South Peat Swamp Forest, Selangor, Malaysia / Hasya Hannani Ruziman and Faezah Pardi - Ruziman, Hasya Hannani; Pardi, Faezah (Faculty of Applied Sciences, 2021)
Kuala Langat South Forest Reserve (KLSFR) was the main highlight when Selangor State Agriculture Corporation proposed to acquire the whole of KLSFR (about 6,908 ha) for the establishment of oil palm plantations. Many parties expressed their concern and opposed the plan as it would lead to the destruction of the forest and its biodiversity. As such, this study was aimed to determine the forest structure and tree species composition to conserve and sustainably manage the forest. Seven plots of 40 m x 20 m covering 0.56 ha were established randomly in KLSFR. All trees with 5 cm diameter breast height (DBH) and above were tagged, measured and identified. Voucher specimens were then taken for further verification purposes. The floristic composition of KLSFR consists of 335 individuals represented by 47 tree species from 21 families. Annonaceae, Guttiferaceae and Myristicaceae were the most speciose families with five species recorded for each family. Goniothalamus malayanus and Koompassia malaccensis were considered to have absolute dominance at the study site with Important Value index of 14.73 % and 14.19 %, respectively. KLSFR recorded low Shannon-Weiner Diversity index of H’ = 2.85 (H’max = 3.81) and Margalef’s Richness Index with DMG = 7.91. Evenness (E) index of 0.75 portrayed that the tree species are almost equally abundant in the study area. Total trees biomass was estimated at 406.90 t/ha, represented by 349.61 t/ha of above ground biomass (AGB) and 57.29 t/ha of below ground biomass (BGB). The study indicated that KLSFR has uniform distribution of individuals with mixed species composition of trees. Tree distribution showed the pattern of De iocourt’s factor procedure (inverse J distribution) where number of tree decreases with the increase in diameter, representing the natural regeneration of the forest.